2014
DOI: 10.1155/2014/394357
|View full text |Cite
|
Sign up to set email alerts
|

Injured Workers Perspectives on Recovery following Non-Life-Threatening Acute Orthopaedic Trauma: A Descriptive Study

Abstract: Background. Little is known about the recovery process following non-life-threatening acute orthopaedic trauma from the viewpoint of the injured person. A better understanding could facilitate optimal rehabilitative planning. Objective. To explore patients' views on factors important to them in recovery following non-life threatening acute orthopaedic trauma. Methods. Descriptive study utilizing content analysis and chi-square analysis. To better understand recovery expectations, 168 adults who had sustained n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…13 Schiller et al interviewed patients following hip fracture who described seeking support, moving more and preserving perspective as the fundamental factors in improving outcome, 26 whereas other studies reported that psychological health was considered by patients as an important marker of recovery. 27,28 Although we did not specifically target questions to determine quality of life factors or personality traits, interestingly, in this population, those discharged home commonly reported that family support and their own strength of mind and determination were the major factors in achieving their goals, whereas those discharged to in-patient rehabilitation seemed to focus on the importance of others in their recovery, often claiming that it was the rehabilitation staff who were the reason for their positive outcome. Locus of control appears to be an individual trait that does not change with different situations, especially with regard to health-related matters.…”
Section: Discussionmentioning
confidence: 99%
“…13 Schiller et al interviewed patients following hip fracture who described seeking support, moving more and preserving perspective as the fundamental factors in improving outcome, 26 whereas other studies reported that psychological health was considered by patients as an important marker of recovery. 27,28 Although we did not specifically target questions to determine quality of life factors or personality traits, interestingly, in this population, those discharged home commonly reported that family support and their own strength of mind and determination were the major factors in achieving their goals, whereas those discharged to in-patient rehabilitation seemed to focus on the importance of others in their recovery, often claiming that it was the rehabilitation staff who were the reason for their positive outcome. Locus of control appears to be an individual trait that does not change with different situations, especially with regard to health-related matters.…”
Section: Discussionmentioning
confidence: 99%